Potencial proliferativo da Acetilcolina em cardiomiócitos - Grisi, Yasmim Estrela Batista (2019)
Cardiovascular diseases continue to be the biggest causes of death in the world for more than a decade, and Acute Myocardial Infarction (AMI) is the most frequently caused by diseases in Brazil. The damage caused by MI is caused by loss of functionality, local inflammatory process, ventricular remodeling, cystic fibrosis, which can culminate in heart failure until death. Strategies to revert this situation are studied and present several lines, and the most discrepant point indicates to be a cardiac regeneration. Acetylcholine (ACh) was subjected to a molecule with cardioprotective, anti-inflammatory effects and that cardiomyocytes have independent machines for the production of acetylcholine, was the main objective of studying whether an ACh has a proliferative role in cardiomyocytes after treatment with pyridostigmine. Observe the behavior in cardiomyocyte cultures of newborn rats from 3 to 5 days, when used with pyridostigmine (PIR), which is an inhibitor of acetylcholinesterase (enzyme that degraded ACh) and keep it modulated in these genes participate in the cell cycle. The chosen genes were Aurora BK, CDK1 and CCND2, data that were analyzed after an RT-PCR and compared with a B-ACTINA normalizer. It was concluded that the results show an ACh proliferative potential when PIR, in 0.1mM and 1mM, in the cardiomyocytes of neonatal rats, modulation of some genes in the cell cycle and potential in the application of treatment in AMI in neonatal rats.